Disability and Social Safety Nets in Developing Countries - Mitra, Sophie (World Bank, Washington, DC, 2012)
The two-way relationship between poverty and disability fosters: disability increases the risk of poverty and the conditions of poverty increase the risk of disability, yet little attention has been given as to whether social safety nets reach persons with disabilities. Social safety nets have a role to play with regard to disability in terms of poverty alleviation, poverty reduction, and development and prevention. The note addresses the way to reach persons with disabilities - to target safety nets based on disability. This approach would benefit persons with such severe disabilities that they cannot participate in the opportunities generated by growth, inclusive employment and/or education policies. These programs might take a number of forms such as: social insurance schemes, publicly funded transfers (sometimes provided as part of a family allowance), in-kind targeting (assistance devices for example) or livelihood programs. However, a more feasible solution may be to ensure that mainstream social safety nets are "disability inclusive". How can mainstream social safety nets be designed, implemented, and evaluated so that persons with disabilities are not excluded? The note describes this process: identification of the physical, social, and communication barriers that prevent the inclusion of persons with disabilities is critical. For instance, do the attitudes of social safety net staff prevent or discourage access to benefits for persons with disabilities?